Strategi Belajar Siswa Kelas VI Untuk Menghadapi Ujian Akhir Sekolah (UAS) Pada SD Negeri 3 Kairatu Kabupaten Seram Bagian Barat - Naomi Telehala; Korlina Makulua; Willem Hetharion (Institut Agama Kristen Negeri (IAKN) Ambon, 2020)
Abstrack: The quality of graduates at the elementary school level is a concern and the main focus of this research is how to apply effective active learning strategies to improve graduate outcomes. According to Rusman, active learning strategies involve more student activities in accessing various information and knowledge to be discussed and studied in the learning process in class so that they get various experiences that can increase their understanding and competence because active learning allows students to develop high-level abilities, such as analyzing and synthesizing. as well as assessing various learning events and applying them in everyday life The method that researchers use to study and analyze this problem is a qualitative method. Furthermore, all the data needed for the discussion is obtained using interview techniques, observation and other documentary data which are considered useful for producing a scientific paper. This data was obtained, analyzed and discussed as a scientific paper with the title